Addressing the Ideal Implementation of Regional Expenditure to Alleviate Poverty: A Case Study of Kebumen Regency - Amrie Firmansyah; Haqqul Fajri Hasibuang; Dina Khairunnisa (IPSAR (International Public Sector Accounting Review), 2023)
The financial relations between the central and local governments face many challenges, and the implementation needs more strengthening and synergism for better decentralization. Law number 1 of 2022 concerning Financial Relations between the Central Government and Local Governments (HKPD Law) is designed to increase society's welfare through effective and efficient spending that provides adequate public service. Kebumen Regency is one of Java's poorest regencies, which has taken enough attention to put more concern on. This study aims to evaluate the regional expenditure implemented by Kebumen Regency Government and explain how it can affect the poverty rate. This study uses a qualitative approach that takes works of literature and existing laws as references to be compared with existing conditions. This study found that the implementation of regional expenditure by the Kebumen Regency government is still not optimal, where the budget allocation is not following mandatory spending provisions. It has led to the Kebumen Regency government being unable to fulfill the Minimum Service Standards for implementing mandatory affairs of basic services, especially in education and health, which is the root cause of the high poverty rate.